Optimal portfolio of European sustainable investment funds based on mean-variance optimization model - Rutenberg, Agustina Paula (2024)
Fil: Rutenberg, Agustina Paula. Universidad Nacional del Litoral. Facultad de Ciencias Económicas; Argentina.